A human ESC-based screen identifies a role for the translated lncRNA LINC00261 in pancreatic endocrine differentiation - Bjoern Gaertner; Sebastiaan van Heesch; Valentin Schneider-Lunitz; Jana Felicitas Schulz; Franziska Witte; Susanne Blachut; Steven Nguyen; Regina Wong; Ileana Matta; Norbert Hübner; Maike Sander (eLife, 2020)
Long noncoding RNAs (lncRNAs) are a heterogenous group of RNAs, which can encode small proteins. The extent to which developmentally regulated lncRNAs are translated and whether the produced microproteins are relevant for human development is unknown. Using a human embryonic stem cell (hESC)-based pancreatic differentiation system, we show that many lncRNAs in direct vicinity of lineage-determining transcription factors (TFs) are dynamically regulated, predominantly cytosolic, and highly translated. We genetically ablated ten such lncRNAs, most of them translated, and found that nine are dispensable for pancreatic endocrine cell development. However, deletion of LINC00261 diminishes insulin+ cells, in a manner independent of the nearby TF FOXA2. One-by-one disruption of each of LINC00261's open reading frames suggests that the RNA, rather than the produced microproteins, is required for endocrine development. Our work highlights extensive translation of lncRNAs during hESC pancreatic differentiation and provides a blueprint for dissection of their coding and noncoding roles.